Otopalatodigital syndrome type 2 in a male infant: A case report with a novel sequence variation - Sankararaman, Senthilkumar; Kurepa, Dalibor; Shen, Yiping; Kakkilaya, Venkatakrishna; Ursin, Sussone; Chen, Harold (Journal of Pediatric Genetics, 2013)
We report a male infant with typical clinical, pathological and radiological features of otopalatodigital syndrome type 2 (OPD 2) with a novel sequence variation in the FLNA gene. His clinical manifestations include typical craniofacial features, cleft palate, hearing impairment, omphalocele, bowing of the long bones, absent fibulae and digital abnormalities consistent with OPD 2. Two hemizygous sequence variations in the FLNA gene were identified. The variation c.5290G>A/p.Ala1764Thr has been previously reported in a patient with periventricular nodular heterotopia, but subsequently it has been reported as a polymorphism. The other variation c.613T>C/p.Cys205Arg detected in the proband has not been previously reported and our analysis indicates that this is a novel disease-causing mutation for OPD2.
Keywords: Otopalatodigital syndrome type 2; FLNA gene; filamin A